Evaluating the performance of four types of photovoltaic panels in Antarctica's extreme environment - Das, Mehmet; Arslan, Erhan; Akpinar, Ebru; Isiler, Dogac Baybars; Ozsoy, Burcu (Elsevier, 2025)
This study experimentally evaluated the performance of four different photovoltaic (PV) systems on Horseshoe Island in Antarctica. The experiment, conducted near the Turkish Scientific Research Camp, examined the efficiencies of monocrystalline, polycrystalline, flexible, and transparent PV panels under summer conditions, while real-time meteorological data such as solar radiation, temperature, humidity, and wind speed were recorded. The power output and surface temperatures of the panels were analyzed, and energy and exergy efficiencies were calculated, along with assessments of environmental impact factors, the exergy sustainability index, and environmental-economic analyses. The power outputs obtained from the experiments were recorded as 14.2W, 13.0W, 12.9W, and 9.2W for monocrystalline, polycrystalline, flexible, and transparentpanels, respectively. The average surface temperatures were determined as 18.3 degrees C for monocrystalline, 18.2 degrees C for polycrystalline, 17.6 degrees C for flexible, and 16.5 degrees C for transparant panels. The highest energy efficiency was observed in the monocrystalline PV panel at 29.1 %, while the efficiencies of the other panels were calculated as 27.0 %, 27.5 %, and 21.5 %, with exergy efficiencies measured at 8.66 %, 8.39 %, 7.37 %, and 6.70 %, respectively. In the environmental analyses, the annual CO2 emission reduction was calculated, with the monocrystalline PV panel providing the highest savings at 4.1 tons. From an economic perspective, the monocrystalline PV panel was also found to be the most advantageous, with a cost of $59. Keywors: Antarctica, Horseshoe, solar panel, enegy-exergy, renewable energy.